Scalable THz Network-On-Chip Architecture for Multichip Systems. (11th December 2020) - Tahanian, Esmaeel; Tajary, Alireza; Rezvani, Mohsen; Fateh, Mansoor
Abstract : While THz wireless network-on-chip (WiNoC) introduces considerably high bandwidth, due to the high path loss, it cannot be used for communication between far apart nodes, especially in a multichip architecture. In this paper, we introduce a cellular and scalable architecture to reuse the frequencies of the chips. Moreover, we use a novel structure called parallel-plate waveguide (PPW) that is suitable for interchip communication. The low-loss property of this waveguide lets us increase the number of chips. Each chip has a wireless node as a gateway for communicating with other chips. To shorten the length of intra- and interchip THz links, the optimum configuration is determined by leveraging the multiobjective simulating annealing (SA) algorithm. Finally, we compare the performance of the proposed THz multichip NoC with a conventional millimeter-wave one. Our simulation results indicate that when the system scales up from four to sixteen chips, the throughput of our design is decreased about 5.8 %, while for millimeter-wave NoC, this reduction is about 21 % . Furthermore, the average latency growth of our system is only 1 % compared with about 40 % increase for the millimeter-wave NoC.